Perancangan Dan Pembuatan Alat Pengendali Pencahayaan Akuarium Berbasis Mikrokontroler - Asnat Khettri Laila; Mega Tri Kurnia (Sistem Komputer & Teknologi Intelegensi Artifisial (SIKOMTIA), 2022)
An important factor in the maintenance of biota for flora and fauna in the aquarium is about lighting the lights to illuminate the aquarium space properly besides being able to invite the attention of connoisseurs of the beauty of skilled craftsmen of aquascape biota. Lighting settings in the aquarium can also be useful for the survival of aquatic animals such as ornamental fish and aquatic plants that adorn the beauty of the aquarium. Good lighting is lighting that allows the biota objects in the aquarium to be seen clearly. Fish keepers or people who come to see the biota in the aquarium sometimes don't, so the lights are on continuously which can lead to a waste of electrical energy. The reason for this research is to design and build a lighting control device for a microcontroller-based aquarium, which can work automatically using the ESP32CAM module with a camera feature to recognize that it is true that there is no object other than a human face with a detected facial object, then the lighting of the aquarium light becomes bright and will die if no facial objects are found around the aquascape aquarium.